Long-term outcomes of adult cryptogenic febrile infection–related epilepsy syndrome (FIRES) - Shi, Xiaojing; Wang, Yuanyuan; Wang, Xuan; Kang, Xiaogang; Yang, Fang; Yuan, Fang; Jiang, Wen (Frontiers in Neurology, 2023)
Background Cryptogenic febrile infection-related epilepsy syndrome (FIRES) is a rare but catastrophic encephalopathic condition. We aimed to investigate the long-term outcome in adult cryptogenic FIRES. Methods This was a retrospective study based on the prospective database in the neuro-intensive care unit of a tertiary hospital in China. Consecutive adult patients with cryptogenic FIRES between July 2007 to December 2021 were included. Long-term outcomes included function independence, the development of drug-resistant epilepsy (DRE), remote recurrent status epilepticus (SE), anti-seizure medications (ASMs), and changes in the brain Magnetic Resonance Imaging (MRI). Results A total of 11 adult patients with cryptogenic FIRES were identified from 270 patients with SE. Four (36%) patients died in the hospital, with three of them withdrawing treatments, and one patient died 12 months after discharge. After the follow-up ranging from 12 to 112 months, 6 (55%) patients were still alive, and all of them achieved functional independence [modified Rankin Scale (mRS) 0-3]. 45% (5/11) patients developed DRE, 18% (2/11) had remote recurrent SE, and 55% (6/11) were on polytherapy with ASMs at the last follow-up. Most of the patients with initial normal or abnormal MRI had abnormalities in the hippocampus at follow-up, and most of the other MRI abnormalities found in the acute stage disappeared over time. Conclusion The outcome of adult cryptogenic FIRES is daunting. More than one-third of patients die in the hospital. Survivors of cryptogenic FIRES may regain functional independence, but they usually develop DRE and receive polytherapy of ASMs for a long time.